Love after Auschwitz: The Second Generation in Germany - Grünberg, Kurt (transcript, 2015)
This book addresses the personal and collective abysses that may open when, albeit many years after the Holocaust, but in the very country of the murderers, one examines the legacy of the National Socialist extermination of Jews. Jewish Lebenswelt in Germany entails involvement of survivors and their sons and daughters, born after the Shoah, with the non-Jewish German world of Nazi perpetrators, supporters, bystanders and their children. Love relationships probably represent the most intimate contact between former victims and perpetrators, or their supporters.This exploration of second-generation relationships in post-National-Socialist Germany is aimed at gaining deeper insights into what Theodor W. Adorno called the »culture after Auschwitz«. The true extent and significance of the chasm that did indeed emerge during the course of this endeavour only became apparent in retrospect. Therefore, an article about the »history« of working on »Love after Auschwitz« has been included.